2020
DOI: 10.37329/cetta.v3i2.453
|View full text |Cite
|
Sign up to set email alerts
|

Pendidikan Karakter Dalam Satua Anak Agung Di Mesir

Abstract: Over the past few years, the government has given a spesific attention to the character education due to its main purpose to develop good and right behaviour for the students since their early age. To achieve this, one of them is through education. In Bali, according to the concept of its society, education is translated by local values in a simple way, such as learning while travelling, learning while singing, learning while playing a game and so on. The Balinese folklore (Satua) is an implementation of Hindu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 1 publication
0
5
0
5
Order By: Relevance
“…Through interviews conducted with the Principal and the student affairs department, it was found that habituation that occurs in the school education environment through routine school activities, spontaneous activities that happen, and exemplary attitudes, students with the maturity of thinking patterns and wisdom of action. This is a vital asset for a person to achieve success (Nugraha, 2020). Education must be able to produce humans with noble characters in addition to adequate academic abilities and skills.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through interviews conducted with the Principal and the student affairs department, it was found that habituation that occurs in the school education environment through routine school activities, spontaneous activities that happen, and exemplary attitudes, students with the maturity of thinking patterns and wisdom of action. This is a vital asset for a person to achieve success (Nugraha, 2020). Education must be able to produce humans with noble characters in addition to adequate academic abilities and skills.…”
Section: Resultsmentioning
confidence: 99%
“…Education must be able to produce humans with noble characters in addition to adequate academic abilities and skills. One way to create people with nature is to integrate character education into every lesson (Nugraha, 2020). From the results of research and interviews with homerooms VII, VIII, and IX, it was found that homerooms and teachers apply the integration of character education in learning to instill good character so that students have a good feeling as a provision for socializing and society.…”
Section: Resultsmentioning
confidence: 99%
“…The year 2023 is excluded because the pursuit started in September 2023, and this year has just ended. Furthermore, today's learning style has also changed, causing the year of publication to be too old and no longer relevant to be used as a reference (Nugraha, 2020). Thus, the period between 2018 and 2022 was selected as the inclusion criteria.…”
Section: Screeningmentioning
confidence: 99%
“…Even though it has entered the new normal, there are several problems that arise including the existence of learning lost in learning 97 activities, the lack of application of character education to students so that it is the task of the government, education personnel and parents to complete these shortcomings. (Firmansyah & Safitri, 2021;Nugraha, 2020;Pakpahan & Fitriani, 2020). This problem is also experienced by some students who are in the researchn Argaheni (2020) Pratiwi, 2020).…”
Section: Introductionmentioning
confidence: 99%